2003
DOI: 10.1111/j.1740-8261.2003.tb00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computed Tomography Renal Angiography for Screening Feline Renal Transplant Donors

Abstract: Preoperative knowledge of the renal vascular anatomy is important for selection of the appropriate feline renal donor. Intravenous urograms (IVUs) have been performed routinely to screen potential donors at the Veterinary Hospital of the University of Pennsylvania (VHUP), but the vascular phase views lack sufficient detail of the renal vascular anatomy. Computed tomography angiography (CTA), which requires a helical computed tomography (CT) scanner, has been found to provide superior renal vascular anatomic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 12 publications
0
29
0
1
Order By: Relevance
“…Arterial anastomosis is most successful if there is a single renal artery with a length prior to branching of at least 0.5cm. If the vascular pedicle has more than one vein, the vein with the longest length and largest diameter is reserved for the anastomosis (Bouma et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Arterial anastomosis is most successful if there is a single renal artery with a length prior to branching of at least 0.5cm. If the vascular pedicle has more than one vein, the vein with the longest length and largest diameter is reserved for the anastomosis (Bouma et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Application of the method to pretreatment imaging of animals with various renal conditions such as neoplasia or vascular malformation associated with hematuria is also envisioned when surgery or embolization are contemplated. In comparing with our previous experience with contrast‐enhanced computed tomography angiography, 1–7 we believe that CE‐MRA is an interesting alternative in that it is faster, potentially safer, and reconstruction/visualization is much easier than with contrast‐enhanced computed tomography angiography. The approach used herein to image the renal vessels can also be applied to other vascular territories.…”
Section: Discussionmentioning
confidence: 79%
“…The acquisition time for each dorsal slab was short enough to prescribe several successive acquisitions of the same volume within one breath‐hold. Based on our previous experience with contrast‐enhanced computed tomography angiography, 1,2 it was estimated that if acquisition was begun at the time of injection of gadolinium, the first pass of contrast medium within the renal arteries would occur during either phase 1 or 2, and the first pass through the renal veins during phase 2 or 3, depending on scanning time per phase. We confirmed that hypothesis although we did not observe a pure arterial enhancement in dog 5, but rather overlapping between the arterial and venous enhancements.…”
Section: Discussionmentioning
confidence: 99%
“…A study in cats reported a 92% agreement between CTA and surgical anatomy of the left renal vasculature . When IVU was used to screen donors, a relatively high incidence (∼10%) of failure to detect unacceptable renal vascular conformation resulted in such detection only at the time of surgery . The low incidence of bilateral multiple arteries, additional cost, and anesthetic considerations may prompt surgeons to refrain from obtaining a preoperative CTA and IVU.…”
Section: Discussionmentioning
confidence: 99%